Penerapan Prinsi Building As Nature Pada Youth Center DiKota Dumai - Muhammad Syifa (Universitas Medan Area, 2020)
Dumai City is a city in Riau Province, Indonesia, about 188 km from Pekanbaru City. Dumai is the city with the third largest administrative area in Indonesia, after the City of Palangka Raya and the City of Tidore Islands. The city started as a small hamlet on the east coast of Riau Province. The average height is 3 meters above sea level. The Dumai City region has a tropical climate with rainfall between 100-300 cm and a temperature of 24-30 ° C with peat swamp soil conditions. In the City of Dumai itself has problems in places where people and some communities gather and family reclamation sites.In this title,